The system reliability analyser tool - Gregoriades, Andreas; Sutcliffe, Alistair G. (My University, 2005)
This paper describes the design and evaluation of a socio-technical design support system, the system reliability analyser (SRA). The tool is used to validate non-functional system requirements, such as system reliability. It employs a Bayesian belief network (BBN) model to assess system reliability (Pearl in Probabilistic reasoning in intelligent systems: networks of plausible information, 1988) based on a variety of high-level operational scenarios. The tool diagnoses problematic areas in future system models and assists in the identification of their causes. The evaluation of the tool demonstrated that it supported the task it was intended to do. The evaluation also identified usability problems in the current visualisations and illustrated their resolution..
Keywords: Bayesian belief networks; Information visualisation; Requirements validation; System reliability